2004
DOI: 10.1021/np0305324
|View full text |Cite
|
Sign up to set email alerts
|

New Glycosides of the Fungus Acremonium striatisporum Isolated from a Sea Cucumber

Abstract: Four new diterpene glycosides, virescenosides R (1), S (2), T (3), and U (4), have been isolated from a marine strain of Acremonium striatisporum KMM 4401 associated with the holothurian Eupentacta fraudatrix. Their structures have been elucidated on the basis of HRFABMS, 1D and 2D NMR (1H, 13C, DEPT, COSY-45, COSY-RCT, HSQC, HMBC, and NOESY spectra), and the results of acidic hydrolysis as 19-O-[beta-D-glucopyranosyl(1-->6)-beta-d-altropyranosyl]-isopimara-7,15-diene-2alpha,3beta-diol (1), 19-O-beta-D-altropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Virescenosides A, B, C, M and N showed cytotoxic effects on developing eggs of sea urchin Strongylocentrotus intermedius with MICs0 range from 2.7 to 20 t, mol L -1 , and their activities decreased in the order of C, M, B, A and N. It was shown that these glycosides exhibited cytotoxic action against tumor cells of Ehrlich carcinoma (ICs0 range from 10 to 100t,molL -1 ) in vitro. Further investigations for metabolites of this fungal strain Acremonium striatisporum KMM 4401 led to the isolation of three new cytotoxic glycosides, virescenosides O, P and Q (43-45 in Fig.3) (Afiyatullov et al, 2002). It was shown that virescenosides O, P and Q exhibited cytotoxic action against tumor cells of Ehrlich carcinoma with ICs0 range from 20 to 100/,mol L -1 in vitro.…”
Section: Bioactive Metabolites From the Fungi Associated With Other Mmentioning
confidence: 97%
“…Virescenosides A, B, C, M and N showed cytotoxic effects on developing eggs of sea urchin Strongylocentrotus intermedius with MICs0 range from 2.7 to 20 t, mol L -1 , and their activities decreased in the order of C, M, B, A and N. It was shown that these glycosides exhibited cytotoxic action against tumor cells of Ehrlich carcinoma (ICs0 range from 10 to 100t,molL -1 ) in vitro. Further investigations for metabolites of this fungal strain Acremonium striatisporum KMM 4401 led to the isolation of three new cytotoxic glycosides, virescenosides O, P and Q (43-45 in Fig.3) (Afiyatullov et al, 2002). It was shown that virescenosides O, P and Q exhibited cytotoxic action against tumor cells of Ehrlich carcinoma with ICs0 range from 20 to 100/,mol L -1 in vitro.…”
Section: Bioactive Metabolites From the Fungi Associated With Other Mmentioning
confidence: 97%
“…Terpene glycosides are a group of natural products with a triterpene or sterol core, and marine diterpene glycosides (MDGs) are a subset of terpene glycosides [66]. Thirty-one new diterpene glycosides, including virescenosides M-R (76-81), R 1 -R 3 (82-84), S-X (85-90), Z (91), and Z 4 -Z 18 (92-106), and three known diterpenic glycosides, virescenosides A (107), B (108), and C (109), together with three known analogues, virescenoside F (110), G (111), a lactone of virescenoside G (112), and the aglycon of virescenoside A (113), were isolated from the fungus Acremonium striatisporum KMM 4401, associated with the sea cucumber Eupentacta fraudatrix, which was collected from Kitovoe Rebro Bay in the Sea of Japan [21,46,[67][68][69][70][71]. Compounds 76, 77, 79, and 107-109 showed cytotoxic effects on developing eggs of the sea urchin Strongylocentrotus intermedius (MIC 50 = 2.7-20 µM) [21,67].…”
Section: Terpenoidsmentioning
confidence: 99%
“…Compounds 76, 77, 79, and 107-109 showed cytotoxic effects on developing eggs of the sea urchin Strongylocentrotus intermedius (MIC 50 = 2.7-20 µM) [21,67]. Compounds 76-81, 85-87, and 107-109 exhibited cytotoxic activities against Ehrlich carcinoma tumor cells (IC 50 = 10-100 µM) in vitro [21,67,68]. Compounds 81 and 85-87 showed weak cytotoxic effects on developing eggs of the sea urchin S. intermedius (IC 50 = 100-150 µM) [68].…”
Section: Terpenoidsmentioning
confidence: 99%
“…Bioassay testing showed that virescenosides M-U (174-182) displayed cytotoxic action against tumor cells Ehrlich carcinoma (IC 50 = 10-100 µM) in vitro. In addition, virescenosides M-N (174-175) and P (177) displayed cytotoxic effects on developing eggs of the sea urchin, Strongylocentrotus intermedius (IC 50 = 2.7-20 µM) (Afiyatullov et al, 2000(Afiyatullov et al, , 2002(Afiyatullov et al, , 2004(Afiyatullov et al, , 2006(Afiyatullov et al, , 2011(Afiyatullov et al, , 2016. Two phenylspirodrimane-type glucosidic meroterpenoids, stachybosides A- B (195-196, Figure 13), were seperated from the sponge-derived fungus, Stachybotrys chartarum MXH-X73 (Ma et al, 2013).…”
Section: Terpenoidsmentioning
confidence: 99%